Fuegian diaspora: The itinerary and agents involved in the construction of Fuegian ethnographic collections carried out by Martin Gusinde through South America and Europe, 1918–1924. Issue 1 (3rd July 2021) - Butto, Ana; Fiore, Danae
ABSTRACT: In this paper, we examine the itinerary of the objects and the agencies involved in the construction of the collections of ethnographic artefacts gathered by German ethnographer and priest Martin Gusinde during his fieldtrips to Tierra del Fuego (Argentina and Chile), carried out between 1918 and 1924. In order to study the formation processes of these collections, we will trace the agencies of the Selk´nam, Yagan and Kawésqar Indigenous people in the making, selling, trading or withholding of their material culture, showing the differential impact these had on the collections. We retrace the dispersal of these Fuegian collections into five museums located in Chile, Austria and the Vatican, presenting a reservoir unknown until now. Our exploration of the complex networks of social and material interactions involved in the dynamic biography of these Fuegian ethnographic collections sheds light on the active role of the Indigenous people in their construction.